Permanent External Biliary Catheter: A Difficult Problem Managed by Rescue Technique of Hepatico-cholecysto-gastrostomy - Singla, Vikas; Yadav, Ajit Kumar; Arora, Anil; Gupta, Arun (Journal of Digestive Endoscopy, 2021)
Percutaneous biliary drainage is commonly performed procedure after failure of ERCP in patients with biliary obstruction. Failure to internalization can lead to permanent external catheter. In the present case, problem of external biliary catheter was solved with hepaticocholecystogastrostomy. Guidewire from the external drain site could not be passed across the stricture, instead it was entering in the gall bladder. This was used as an opportunity to internalize the catheter. First EUS guided cholecystogastrostomy was performed, followed by placement of stent between right biliary system and the stomach, through the cholecystogastrostomy stent. This led to drainage of right biliary system into the stomach, and the external catheter could be removed.
Keywords: cholecystogastrostomy; endoscopic ultrasound; permanent external biliary catheter